Efek Pemanfaatan Website pada Pelajaran Pemasaran Online untuk Meningkatkan Motivasi Belajar Siswa SMKN 2 Sidrap - Zulkifli N; Handy Ferdiansyah (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2023)
This quantitative study aims to determine the success rate of using the website as a means of learning online marketing practicum at SMK Negeri 2 Sidrap in order to increase student learning motivation. The population in this study is all students majoring in Online Business and Marketing (BDP) which amounted to 81 students, while the sampling referred to opinions, from these opinions, the number of samples used as respondents in this study was 81 people. To collect data on this study, researchers used observational methods and questionnaires, research questionnaires were provided in the form of google forms. Questionnaires are given to teachers and students to find out the response to the use of websites in learning online marketing practicums. The data analysis technique in this study was using the IBM SPSS Statistics 22 Application. Data analysis techniques using wilcoxon analysis were performed to see the extent of the influence of independent variables on dependent variables. Based on the research findings, it is known that the application of online marketing learning was successfully carried out using the Google website, according to the research findings. This is evidenced through the results of the analysis of student responses to the use of google sites web in online marketing lessons related to student learning motivation when using google sites web media through the wilcoxon test, which means that the ho is 7,827 with a value of sig.2 tailed 0.000 0.005 which means that hotyling is notified. It can be concluded that there is an influence of website utilization on online marketing lessons to increase the learning motivation of smkn 2 Sidrap students between before and after the intervention.